POTENTIAL USE OF SHALLOTS SKIN EXTRACT AS SEED PRIMING TO INHIBIT DETERIORATION AND INCREASE VIABILITY OF SOYBEAN SEEDS - Suryaman, Maman; Sunarya, Yaya (LPPM Universitas Jambi, 2026)
Soybean seeds, compared to other grain crops, deteriorate quite quickly, lose its vigor and yield. Therefore, proper measures are required to enchance seeds viability and prevent deterioration. The study is to investigate the potential of shallot skin extract in enchancing viability and preventing deterioration of soybean seeds. A factorial completely randomized design that was duplicated three times was employed in the study. The first factor was concentration of shallots skin extract of 0, 10, 20, and 30%, and the second factor was soaking time of 1, 3, and 6 hours. Electric conductivity, seed viability, vigor index, germination rate, and dry weight of sprouts were the observed data that were subjected to Analysis of Variance and Duncan's multiple range test at α 5%. The results indicated that soaking the seeds in 10% shallot skin extract for six hours showed the lowest level of electric conductivity. Compared to the control, the simple effect of increasing the concentration of shallot skin extract by 10, 20, and 30% enhanced the dry weight of sprouts, germination rate, vigor index, and seed vigor. In conclusion, soaking soybean seeds in shallot skin extract may preserve seed viability and prevent degradation, although the soaking time had no significanct effect on seed viability. The shallot skin extract can be used as seed priming agent to improve viability of soybean seeds affordable to the farmers.